Domestic violence: The day-to-day life of peruvian women experiencing depressive disorders - Josefina Amanda Suyo-Vega; Mónica Elisa Meneses-La-Riva; Susana Edita Paredes-Díaz; Víctor Hugo Fernández-Bedoya (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
Violence against women in Peru is on the rise, with 138% of femicides recorded by women's emergency centers by 2018. Mental health with depressive disorders is the leading cause of health problems worldwide, according to the World Health Organization. The objective was to determine the prevalence of domestic violence and depressive disorders among women in three departments of Peru. The methodology was applied, with a quantitative approach, of non-experimental design, of a cross-sectional nature. The population consisted of 384 women over 18 years of age, distributed in Lima 250, La Libertad 80, and Amazonas 54, where they reported mistreatment and depressive disorders, information recorded in the Women's Emergency Centres, the police stations, the Vaso de Leche social programs, the canteens and the Office of the Ombudsman for Women, Children, and Adolescents. The data collection technique was a survey, the instruments applied were two questionnaires, one measuring the prevalence of domestic violence (VIF J4), and the Hamilton Scale for depressive disorder, which suggests the following cut-off points: not depressed, mild/minor depression, moderate depression, severe depression, and very severe depression. Among the relevant results, it was found that of the 100% of women who suffer from domestic violence, these are subdivided into physical violence 16%), psychological violence 20%, sexual violence 26%, social violence 16%, patrimonial violence 11% and gender violence 13%. For the depressive disorder, it was found that 100 percent of women who suffer from domestic violence have depressive disorders divided into intermediate insomnia 4%, early insomnia 7%, late insomnia 7%, women who suffer in the development of their activities and work 8%, depressive mood 14%, thoughts about suicide (15/100), psychomotor inhibition 15%, and psychomotor agitation 15% that concluding that domestic violence associated with depressive disorders leads to suicide.